Closing the management competence gap - Filerman GL (BMC, 2003)
Abstract The success of any organized health program depends upon effective management, but health systems worldwide face a lack of competent management at all levels. Management development for health systems, particularly at the first line of supervision, must be given much higher priority by senior leaders and for investment. Human resource development leaders must be the advocates for making the investment in managerial competence.